(untitled) (Economics and region, 2020)
In the article is defined that modern management of competitiveness of region should be directed on creation and use of regional competitive advantages, mutually advantageous relations with domestic and foreign economic subjects, public authorities and local governments, subjects of business. Achievement of positive influence of institutional factors of regional competitiveness sets before the policy of the state and the region the necessity to solve a set of strategic tasks, the main of which are the following: strengthening of legal and financial foundations of the regional level of management and local self-government; consolidation of regional subjects around the idea of competitiveness; taking into account the values of the region’s population in the development of regional development programs; strengthening of labor motivation in the system of regional management and local self-government; strengthening of labor motivation in the system of regional development.